Predictive value of hematological parameters in testicular salvage: A 12-year retrospective review - Chen, Pengyu; Huang, Weipeng; Liu, Lei; Chen, Nana; Zhou, Guanglun; Sun, Mengkui; Li, Shoulin (Frontiers in Pediatrics, 2022)
Purpose This study aimed to evaluate the predictive value of preoperative hematological parameters for testicular salvage in patients with testicular torsion. Methods Clinical data of patients with testicular torsion treated at Shenzhen Children's Hospital from January 2010 to December 2021 were analyzed retrospectively. The data collected included age, symptom duration, degree of spermatic cord torsion, the surgical approach adopted, hematological parameters, and ultrasound results during postoperative follow-up. Results The study participants were classified into three groups as follows: the successful testicular salvage group (n = 43), failed testicular salvage group (n = 124), and control group (n = 100). Univariate analysis showed that testicular salvage was related to patient age, duration of symptoms, spermatic cord torsion degree, white blood cell count, lymphocyte count, monocyte count, platelet-lymphocyte ratio, and neutrophil-lymphocyte ratio. However, multivariate analysis revealed that symptom duration (OR = 0.948, P < 0.001), degree of spermatic cord torsion (OR = 0.994, P < 0.001), and monocyte count (OR = 0.020, P = 0.011) were independent risk factors for testicular torsion salvage. The monocyte count in the failed salvage group was significantly higher than in the successful salvage and control groups (P < 0.01). Conclusion Monocyte count is an independent predictor of testicular salvage. Therefore, clinicians can predict the success rate of testicular salvage in patients with testicular torsion based on the monocyte count.